A critical perspective on ecological unequal exchange, dependency and development - Isakson, Alberto (2016)
Chile is strongly interconnected to the global markets through its trade relations. From a monetary perspective the country has shown an outstanding trade performance, having an equilibrated trade balance, avoiding debts and even presenting periods with high surplus. Nonetheless, the products Chile trade have embodied great social and ecological impacts. Thus, from a social and ecological perspective, Chile’s positive trade performance is being challenged. Ecological Unequal Exchange (EUE) is a theory that precisely analyses these dimensions in trade. However, EUE has several limitations that must be discussed and overpassed. This thesis, through a deep theoretical discussion and a detailed empirical study on Chile’s trade relations between 1960 and 2014, builds a critical analysis to EUE theory and its accuracy in explaining the issues related to trade and its consequences for the trading countries. This study concludes that depending on the EUE approach used, Chile can have or not have EUE relations. Furthermore, this thesis shows that strict-approaches to EUE fall short in explaining the complex interactions and consequences of trade. Therefore, a critical or relative-EUE approach is proposed, emphasising the impacts global relations has on local realities to understand the consequences of trade and achieve a more sustainable development.